Preferred and Avoided Temperatures of the Prawn Macrobrachium Acanthochirus (Crustacea, Palaemonidae) - Hernández Díaz, Arnulfo; Buckle, Fernando; Espina, Sonia (Boletín del Centro de Investigaciones Biológicas)
This study determined thermoregulatory behavior of prawns (Macrobrachium acanthochirus) in relation to thermal conditions of their natural environment (20-28°C). Preferred temperatures (PT) and avoided temperatures were measured in a thermal gradient for organisms acclimated to 23, 26, 29, and 32°C. The acute thermal preference (25.7°C) was obtained graphically and by linear regression: PT = 36.304 - 0.414 AT Ó 0.15°C, where AT is the acclimation temperature. The model was highly significant (P = 0.028, R2 = 0.996). To define the relationship between high avoided temperatures (HAT) and low avoided temperatures (LAT) and AT, the following regressions were calculated: HAT = 43.333 - 0.567 AT Ó 0.39°C (P = 0.010, R2 = 0.980), and LAT = 38.0 - 0.60 AT Ó 0.63°C; (P = 0.024, R2 = 0.953). Prawns acclimated at low AT had high PT values and vice-versa. At intermediate temperatures, the differences between AT and PT were negligible. A similar pattern was observed for the avoided temperatures. Specific thermal efficiency (STE) of the prawns is 77.5%. Therefore, cultivation of M. acanthochirus is recommended at locations where most frequent temperatures are near the thermal preferendum for this species. The range of M. acanthochirus expands 250 km northward to Jalisco State and altitudinally to 600 m. Previously, the species was known to occur from the State of Oaxaca to the southern part of Colima State.